Broken Home Students' Analysis of the Linguistic Development of Elementary School Students - Lusiyanna Lusiyanna; Siti Nurjanah; Khosyim Mawardi (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to determine the impact of broken-home families on student behavior at MI Darussalam Bumi Agung. The research used a qualitative method. Data were collected through observation, documentation, and interviews. From these data, the researcher concluded that broken-home backgrounds have a severely negative effect on the development of speaking, writing, reading, and listening skills. The study was a field investigation carried out in February–March 2026 at MI Darussalam Bumi Agung. It employed qualitative research, using descriptive methods to obtain findings about linguistic development phenomena in children from broken-home families. The subjects of the study were a fourth-grade child with a broken-home background at MI Darussalam Bumi Agung, identified by the initial M; the student's guardian, A; and the class guardian, N. Data collection techniques included direct observation, in-depth interviews with the parent, and documentation. The results indicate that: 1) student M has problems in linguistic development compared with peers in general. Causes include limited involvement from the single parent (father), who is busy with work and gives insufficient attention to M; 2) M experiences linguistic development difficulties such as reading difficulties and low confidence in speaking and storytelling. The findings reveal that family and social-environmental factors play a crucial role in advancing a child's language abilities. Therefore, contributions from parents, educators, and the community are essential to provide stimulation and early intervention to prevent speech delays. This study is expected to serve as a reference for improving understanding and analysis of broken-home students' linguistic development at MI.